Homo-AMPA in the periaqueductal grey modulates pain and rostral ventromedial medulla activity in diabetic neuropathic mice. (1st July 2022) - Palazzo, Enza; Boccella, Serena; Marabese, Ida; Perrone, Michela; Belardo, Carmela; Iannotta, Monica; Scuteri, Damiana; De Dominicis, Emanuela; Pagano, Martina; Infantino, Rosmara; Bagetta, Giacinto; Maione, Sabatino
Abstract: The 2-amino-4-(3-hydroxy-5-methylisoxazol-4-yl)-butyric acid, homo-AMPA, an analog of α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) and 2-aminoadipic acid, has shown no activity towards ionotropic and metabotropic glutamate 1, 2, 3, 4, 5, and 7 receptors (mGluR1-7), agonist activity at mGluR6 while the activity at mGluR8 was never investigated. The effect of homo-AMPA on pain control has been never investigated. In this study we evaluated the effect of intra-ventrolateral periaqueductal grey (VL PAG) microinjections of homo-AMPA on pain responses and the activity of pain-responding neurons of the rostral ventromedial medulla (RVM), the "pronociceptive" ON cells, and the "antinociceptive" OFF cells. The study was performed in control and diabetic neuropathic mice. Homo-AMPA decreased mechanical allodynia in diabetic neuropathic mice. Homo-AMPA increased also the latency to tail-flick, decreased the ongoing activity, the pain stimulus-evoked burst of firing, and the duration of the burst of the ON cells in both, control and neuropathic mice. Homo-AMPA also increased the ongoing activity, decreased and delayed the pause of the OFF cells in control mice. Unlike the retina, we did not find the transcript and protein for mGluR6 in the VL PAG. Alpha-methyl-serine-O-phosphate, a group III mGluRs antagonist, blocked the anti-allodynic effect of homo-AMPA. Considering the absence of both, mGluR6 in VL-PAG and homo-AMPA activity at mGluR4 and mGluR7 at the dose used, mGluR8 could be the target on which homo-AMPA produces the observed effects. The target of homo-AMPA capable of evoking analgesia at a very low dose and in conditions of diabetic neuropathy deserves further consideration. Graphical abstract: Image 1 Highlights: Homo-AMPA is described as a mGluR6 selective agonist. Homo-AMPA in the VL PAG inhibited pain in control and diabetic mice. Homo-AMPA decreased the activity of the RVM ON cells in control and diabetic mice. Homo-AMPA increased the activity of the antinociceptive OFF cells in control mice. No transcripts for mGluR6 were found in the VL PAG.